Introduction: Understanding Thailand's Politics. Issue 3 (2nd July 2016) - Kanchoochat, Veerayooth; Hewison, Kevin
ABSTRACT: Thailand's politics from the mid-2000s has seen considerable conflict and contestation, with seven prime ministers, two military coups, and scores of deaths from political violence. This article, as well as introducing the eight articles in the Special Issue, examines various aspects of this tumultuous period and the authoritarian turn in Thai politics. It does this by examining some of the theoretical and conceptual analysis of Thailand's politics and critiquing the basic assumptions underlying the modernisation and hybrid regimes perspectives that have tended to dominate debates on democratisation. While the concepts of bureaucratic polity and network monarchy shed light on important political actors in Thailand, they have not grappled with the persistence of authoritarianism. In theoretical terms, the article suggests that it is necessary to understand historically specific capitalist development as well as the social underpinnings that establish authoritarian trajectories and reinforce the tenacity of authoritarianism.